Norway : Financial Sector Assessment Program-Technical Note-Risk Analysis and Stress Testing. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
Much of the work of the FSAP was conducted prior to the COVID-19 outbreak. The risk and vulnerability analysis integrates the original work with a quantification of the impact of the COVID-19 crisis on bank solvency under two separate scenarios. The original 'market shock' scenario explores additional risks that feature less prominently in the COVID scenarios.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet